Self-Concept and Time Perspective of Convicts - Kuatov, Azat K.; Abibulayeva, Aizhana B.; Kuatova, Ayazhan S.; Kashhynbay, Baizhuman B. (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
Objective: The purpose of the article is to connect the time perspective of the convicts with their self-concept. Background: After an extended stay in places of deprivation of liberty, it is difficult for convicts to adapt to the conditions of life in freedom, to restore the social ties that were lost and weakened due to isolation. And therefore, they often fall into the marginal part of the population, cannot find their place in life, and often replenish the number of unemployed or, even worse, re-enter the criminal path and commit crimes. Method: The following psychological methods were used: the technique of “Who am I?”, which allowed studying the cognitive component of the self-concept; the methodology of personal differential that provides an opportunity to study the emotional component of the self-concept; the self-attitude test questionnaire and the method of F. Zimbardo allowed to determine the main features of the time perspective. Results: The article reflects the study of convicts based on which a typology of “self-concept” of convicts was proposed. Besides, the results of a study of the temporal perspective of convicts depending on the type of self-concept are presented. Conclusion: The authors are inclined to believe that a detailed study of this problem will identify and provide effective ways to stimulate the constructive resocialization of various categories of prisoners.